(untitled) (Journal of Economic Research & Business Administration, 2016)
In times of globalization, the main task in all countries is to formulate and maintain the competitiveness of the private economic entities and the national economy. Given the variety of market kriteriy6 explores new ways to improve the domestic economic opportunities and increase productiv ity. Every day a growing demand for new products and new production. Competitiveness – is not only the value of the parameter and the quality of manufactured goods, as well as innovation management and invest ment activities.